Prevalence of HBV Infection and Associated Risk Factors in the General Population of District Peshawar, Pakistan - Aziz, Samar; Akbar, Asma; Iqbal, Sheeza; Tawab, Faiza; Inayat, Naila (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to assess the prevalence of hepatitis B virus (HBV) infection and its associated risk factors in the general population of Peshawar, Khyber Pakhtunkhwa (KPK), Pakistan. Methodology: This cross-sectional study was conducted at Khyber Teaching Hospital and Lady Reading Hospital, Peshawar, from December 2023 to July 2024. Data were collected through structured questionnaires administered to 200 patients who tested positive for HBV. The study sample included 143 males (71.5%) and 57 females (28.5%). Results: Among the 200 patients, HBV infection was more prevalent in males (71.5%) compared to females (28.5%), with the highest infection rate observed in the 21–40 age group. The majority of HBV-positive cases were found among patients of middle and lower socioeconomic status. Common symptoms included abdominal pain, fever, pale stool, and dark urine. Key risk factors identified were smoking (35%), unsafe blood transfusion (28%), and razor sharing (42%). Conclusion: HBV infection rates were significantly higher in males than in females, potentially due to risk factors like smoking, razor sharing in barber shops, and unsafe blood transfusions. These findings underscore the importance of targeted public health interventions to reduce HBV transmission in Peshawar.